The concentration of calprotectin in the stools of children with diagnosed cystic fibrosis - Sabina Więcek; Halina Woś; Bożena Kordys-Darmolińska; Magda Sankiewicz-Szkółka; Urszula Grzybowska-Chlebowczyk (Gastroenterology Review)
Introduction: Calprotectin is a protein that plays a regulatory role in inflammatory reactions as an antibacterial and antiproliferative factor. Aim : To assess the concentration of calprotectin in the stools of patients with diagnosed cystic fibrosis. Material and methods: Forty-one patients were included in the study, 24 boys and 17 girls, aged from 7 weeks to 18 years. The concentration of calprotectin in stools was assessed with the ELISA method. The analysis included clinical symptoms and the results of laboratory tests and the type of mutation. Results : An elevated level of calprotectin in the stool was observed in 4/41 (9.7%) patients, mainly in older children, and mainly delta F508/deltaF508 mutation. The correlation between the concentration of calprotectin and clinical symptoms, age, increased indicators of an inflammatory process, levels of protein and aminotransferases in blood serum and the values of acid steatocrit of the stool was not proven. Conclusions : High concentrations of calprotectin in the stools of children with diagnosed cystic fibrosis do not correlate with the level of advancement of lesions within the gastrointestinal tract. Elevated concentrations of calprotectin in the stools of patients with cystic fibrosis may indicate inflammation of intestine and should be further scrutinised.